Interleukin 4 haplotypes of susceptibility to chronic periodontitis are associated with IL-4 protein levels but not with clinical outcomes of periodontal therapy - Anovazzi, Giovana; Finoti, Livia S.; Corbi, Sâmia C.T.; Kim, Yeon J.; Marcaccini, Andrea M.; Gerlach, Raquel F.; Capela, Marisa V.; Orrico, Silvana R.P.; Cirelli, Joni Augusto [UNESP]; Scarel-Caminaga, Raquel M. (Elsevier, 2013)
Different IL4 haplotypes were associated to susceptibility to/or protection against chronic periodontitis (CP). The aim of this study was to investigate if individuals carrying different haplotypes would present differences in clinical periodontal parameters and in the IL-4 levels at baseline, 45 and 90 days after non-surgical periodontal therapy. 62 patients were subdivided: genetically protected without CP (PH), genetically protected with CP (PCP), genetically susceptible with CP (SCP), genetically susceptible without CP (healthy) (SH). Clinical examination and gingival crevicular fluid (GCF) collection were performed for all patients, and IL-4 levels were measured by ELISA. At baseline, higher values for plaque index (PI, p = 0.013), gingival index (GI, p = 0.005) were observed for the SCP group in comparison to the PCP group but not after the completion of periodontal therapy. 45 and 90 days after the non-surgical therapy, PCP demonstrated significantly higher IL-4 levels than the SCP (p = 0.000002). Correlation analysis showed different results between clinical parameters and IL-4 production or GCF volume for groups with different genetic loads. The IL4 gene which was previously associated with susceptibility to CP was related with differences in the IL-4 protein levels in the GCF. However, independent of genetic carriage, individuals responded similarly to this therapy. © 2013 American Society for Histocompatibility and Immunogenetics.